Evaluation of the KLauS ASIC at low temperature - Wang, Wei; Shen, Wei; Yuan, Zhenxiong; Briggl, Konrad; Schultz-Coulon, Hans-Christian; Warttmann, Erik; Yan, Wenqi; Cao, Guofu; Li, Zepeng; Qi, Ming; Wen, Liangjian (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2021)
The Taishan Antineutrino Observatory (TAO) is proposed to first use a cold liquid scintillator detector (−50 °C) equipped with large-area silicon photomultipliers (SiPMs) (∼10 m2) to precisely measure the reactor antineutrino spectrum with a record energy resolution of ¡ 2% at 1 MeV. The KLauS ASIC shows excellent performance at room temperature and is a potential readout solution for TAO. In this work, we report evaluations of the fifth version of the KLauS ASIC (KLauS5) from room temperature to -50 °C with inputs of injected charge or SiPMs. Our results show that KLauS5 has good performance at the tested temperatures with no significant degradation of the charge noise, charge linearity, gain uniformity or recovery time. Meanwhile, we also observe that several key parameters degrade when the chip operates in cold conditions, including the dynamic range and power consumption. However, even with this degradation, a good signal-to-noise ratio and good resolution of a single photoelectron can still be achieved for the tested SiPM with a gain of greater than 1.5 × 106 and even an area of SiPM up to 1 cm2 in one channel, corresponding to an input capacitance of approximately 5 nF. Thus, we conclude that KLauS5 can fulfill the TAO requirements for precise charge measurement.